2019
DOI: 10.9734/mrji/2019/v28i330133
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bacterial and Anti-fungal Properties of Garlic Extract (Allium sativum): A Review

Abstract: Garlic (Allium sativum) contains various biologically active components that play a significant role in the treatment of bacterial and fungal infections. It contains sulfur compounds like allicin, ajoene, allylmethyltrisulfide, diallyltrisulfide, diallyldisulphide and others which exhibit various biological properties like antimicrobial, anticancer, antioxidant, immunomodulatory, anti-inflammatory, hypoglycemic and cardiovascular effects. The objective of the current review was to relate various literatures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 9 publications
4
10
0
1
Order By: Relevance
“…The interaction energies evaluated from in-silico tests using garlic phytochemicals against 1,3-beta-glucan synthase (PDB ID: 4m80) revealed that all nine garlic phytochemicals interacted with 1,3-beta-glucan synthase. Garlic phytochemicals have good antifungal properties, and it has been observed in many studies that they work by interrupting the fungal cell wall [12][13][14][15][16][17]. Similarly, the results of our investigation suggest that garlic phytochemicals can have a good impact on black fungi.…”
Section: Discussionsupporting
confidence: 77%
“…The interaction energies evaluated from in-silico tests using garlic phytochemicals against 1,3-beta-glucan synthase (PDB ID: 4m80) revealed that all nine garlic phytochemicals interacted with 1,3-beta-glucan synthase. Garlic phytochemicals have good antifungal properties, and it has been observed in many studies that they work by interrupting the fungal cell wall [12][13][14][15][16][17]. Similarly, the results of our investigation suggest that garlic phytochemicals can have a good impact on black fungi.…”
Section: Discussionsupporting
confidence: 77%
“…Garlic phytochemicals have good antifungal properties, and it has been observed in many studies that they work by interrupting the fungal cell wall. (13)(14)(15)(16)(17)(18) Similarly, the results of our investigation suggest that garlic phytochemicals can have a good impact on black fungi. All the phytochemicals showed signi cant binding energies during blind docking.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, garlic extract was found to inhibit the Meyerozyma guilliermondii and Rhodotorula mucilaginosa germination and growth [55]. Another study reported the antifungal activity of various A. sativum extracts namely aqueous, ethanolic, methanolic, and petroleum ether against human pathogenic fungi such are Trichophyton verrucosum, T. mentagrophytes, T. rubrum, Botrytis cinerea, Candida species, Epidermophyton floccosum, Aspergillus niger, A. flavus, Rhizopus stolonifera, Microsporum gypseum, M. audouinii, Alternaria alternate, Neofabraea alba, and Penicillium expansum [56]. The garlic extract acted by affecting the fungal cell wall and causing irreversible ultrastructural changes in the fungal cells, which lead to loss of structural integrity and affected the germination ability.…”
Section: Antifungal Activitymentioning
confidence: 99%